Regioselective functionalization of pyrones: Facile synthesis of 6-styrylpyrones via KHMDS-mediated aldol condensation. (5th January 2022) - Samala, Ramakrishna; Basu, Manas K.; Mukkanti, K.
Graphical abstract: Highlights: KHMDS-mediated aldol condensation to access 6-styrylpyrones from pyrones. Excellent regio- and stereoselectivity. Good substrate scope. Moderate to good yields. Successfully applied for the synthesis of natural products asnipyrone A and B. Abstract: Herein, we disclose our efforts directed toward the synthesis of the kavalactone-based natural product penstyrylpyrone and other related 4-OMe-2-pyrones possessing diverse substituents at the 3-, 5-, and 7-positions. Further, a facile approach to access 6-styrylpyrones via the KHMDS-mediated regioselective aldol condensation of 2-pyrones is described with moderate substrate scope and good to high yields (58–80%). The utility of this methodology was exemplified by the stereoselective construction of desmethoxyyangonin, asnipyrone A, and asnipyrone B.